The rising trend of green protectionism: Biofuels and the European Union - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2012)
This paper surveys and discusses the Renewable Energy Directive (RED) in the European Union and its compatibility with EU obligations in the World Trade Organisation (WTO). More particularly, it intends to shed light on the evolvement of policies in Europe to protect biofuels producers from foreign competition. While the effectiveness of traditional protective tools of trade policy - tariffs and subsidies - are diminishing, local producers have embraced the introduction of specific sustainability criteria that would have the effect of protecting incumbent market actors while increasing the cost for new foreign market entrants. (...)
Keywords: 330; Biokraftstoff; Umweltpolitik; Protektionismus; EU-Staaten